ENKAPSULASI SERBUK SIMPLISIA DAN EKSTRAK KULIT JERUK SERTA APLIKASINYA PADA VEGETABLES JAM - Gloria Angelina; Elisabeth Tyastiningrum; Ester Mastiur Sitorus; Nur Aini (JURNAL AGROTEKNOLOGI, 2021)
Mandarin peel contains essential oil with limonene as the dominant compound that can be used as a flavor additive and source of antioxidants in food products. Vegetables jam is an innovation of vegetable processing that requires flavor additive to increase its acceptability and quality. The aim of this study was to determine formulation, sensory, and chemical characteristics of vegetables jam with addition of encapsulated mandarin peel simplicia powder and extract. The factors that used in this study are type of active substance [simplicia powder (A1) and extract (A2)] and proportion of maltodextrin and arabic gum [1:3 (E1), 2:3 (E2), 3:3 (E3), 3:2 (E4) and 3:1 (E5)]. Based on the results of the study, vegetables jam with addition of encapsulated essential oil extract with proportion of maltodextrin and arabic gum 2:3 (A2E2) was the best treatment, where the sensory evaluation consisted of color has a score of 3.67 (orange-green to greenish orange), aroma 3.53 (slightly typical of jam to typical of jam), taste 3.00 (slightly sweet), smearing power of 4.53 (average to very average), total liking of 3.4 (slightly like to like), the water content of 77.32%, the antioxidant activity of 7.75%, beta carotene content of 15017.99 μg/100 g, and total dietary fiber content of 0.62%. Keywords: encapsulation, extract, mandarin peel, simplicia powder, vegetables jam